The Maternal Risk Factors Analysis Based on The Type of Refferal Senders - Suryani Yuliyanti; Fitri Rahmawati; Ratnawati Ratnawati (JURNAL KEBIDANAN, 2023)
The obstetric emergency referral system is intended to handle pregnancy emergencies quickly, precisely, efficiently, and effectively by the capabilities and authorities of health care facilities. This condition is reflected by sending referrals following the established risk factor diagnosis. The purpose of this study was to determine the differences in maternal risk factors based on the type of referral sender’s health facility. A cross-sectional study was conducted in 2018-2019 taking 113 cases of referral deliveries at the Sultan Agung Islamic Hospital in Semarang. Referral senders are divided into three groups consisting of 1) private practice midwives, 2) primary health care, primary health clinics, general practitioner, type D hospitals, and 3) type C hospitals. The risk factors of pregnancy are divided into three categories such as low, high, and very high-risk pregnancies. Very high-risk pregnancy was the most dominant finding in each referral sending health facility. The very high-risk pregnancy rate that comes from private practice midwives is 62.5%; from the primary health centers, type D hospitals, clinics, and general practitioner is 57.9%, and 92.9% came from type C hospitals. Based on the fisher’s exact test, there is no difference in maternal risk factors based on the sender’s referral (p-value of 0.187). It is necessary to review and harmonize tiered referral regulations with regional health regulations, so that the referral system can be implemented effectively and efficiently.